PERBEDAAN KEMAMPUAN KEUANGAN DAERAH DI INDONESIA - Lara Erfiana; Siti Aisyah (JURNAL FAIRNESS, 2022)
The purpose of this study is to examine the differences in financial capacity of the district / city and the expansion in Indonesia. The data used in this study are secondary data obtained from the district / city APBD in Indonesia accessed from the website of the Ministry of Finance Republic of Indonesia Budget Director General. The number of parent districts / cities and expansion district is 280. Data analysis methods used are descriptive analysis and different test. The results of the research obtained are: (1) The independence ratio of the main districts / cities and expansion district is not significantly different. This means that regional independence in the main district / city and division in Indonesia is relatively similar, where the two groups of regions still have low independence; (2) The ratio of the degree of fiscal decentralization between the districts / cities of the parent and expansion district occurs differences. This shows that between the parent’s district and expansion district have relatively different financial capabilities and the two regional groups still have a high dependence on the central government; (3) The ratio of the activity of the main district / city and division has a significant difference. This shows that the district / city parent has a high activity ratio in regional development, where the allocation of regional expenditures is relatively larger compared to the newly created districts / cities; (4) Routine capability ratios in the parent / city and expansion district have significant differences. This shows that the parent districts / cities have higher routine capability ratios compared to newly created districts / cities. This condition can be seen from the total routine expenditure allocated by the parent district / city; and (5) The growth ratio in the parent regency / city and expansion district has a significant difference. This shows that the parent districts / cities have a higher ability to receive their PAD compared to the newly created districts / cities.